Chapter 6: Challenges in Fire Investigation - Johnson, Stephen; Harrison, Karl; Dean, Jason (Royal Society of Chemistry, 2021)
This chapter introduces what fire investigation is and why it is necessary. It explores, through a case study and analysis of key issues, the challenges that are faced by fire investigators and those who support them. It finishes with some of the general problems for fire investigation and the more specific issues related to the chemistry of fire scenes.
Book Title: Challenges in Detection Approaches for Forensic Science
Keywords: Forensic science; Fire; Investigation; Detection